A Lesbian in the punditry - Reed, Jennifer (Journal of Lesbian Studies, 2010)
This article argues that Rachel Maddow has become one of a growing number of new public lesbians. This is a subject position that makes no secret of or apology for lesbian identity. Nor does it seek to make explicit political claims for liberation or separation. Maddow uses this subject position as host of her own cable news show, The Rachel Maddow Show, combined with her presence in other media, where she presents as a butch lesbian and comments on her more conservative look on her television show, to create a lesbian presence that disrupts heteronormativity, offers alternatives to heterogender, and in particular as a news show, tells a more inclusive liberal humanist story.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; communication; discipline; hétérosexisme; médias; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; états-unis